Relationship Between Duodenal Histopathology and Strong Positive Tissue Transglutaminase Antibodies in Children with Celiac Disease - Güzide Doğan; Semin Ayhan; Pınar Erbay Dündar (Güncel Pediatri)
Introduction: In celiac disease (CD) strong positive tissue transglutaminase antibody (TTGA) levels (≥100 U/A) have been shown to almost always indicate villous atrophy. The aim of this study is to determine the sufficiency of ≥100 U/A Ig A type TTGA levels for diagnosis of CD.Materials and Methods: Results from duodenum biopsy performed due to positive TTGA in 197 children were retrospectively examined. IgA TTGA levels had a positive value of >18 U/A. Increases of 5 times or more than this threshold value (≥100 U/A) are accepted as strong positivity. CD diagnosis was made according to ESPGHAN criteria. A modified Marsh stage ≥2 was accepted as significant for CD. Results: Of the cases, 129 were female (65.5%) and 68 were male (34.5%). Duodenum histopathology was compatible with Marsh 0 for 1 case (0.5%), Marsh 2 for 17 cases (8.6%), Marsh 3a for 41 (20.8%), Marsh 3b for 81 (41.4%) and Marsh 3c for 57 (28.9%). The TTGA levels of 64 of the 197 cases (32.5%) were ≥100 U/A. In cases with strong positivity for TTGA the duodenum histology was compatible with Marsh 3 (villous atrophy) for 63 and Marsh 0 (normal histology) for 1 case (type 1 diabetic and asymptomatic for CD). For Marsh 3c TTGA levels ≥100 U/A had a sensitivity of 85.96% (95% CI: 74.2-93.7%), specificity of 89.29% (95% CI: 82.9-93.8%), positive predictive value of 76.56% (95% CI: 64.3-86.2%) and negative predictive value of 93.9% (95% CI: 88.4- 97.3%). Conclusions: This study showed that positive IgA TTGA levels (≥100 U/A) were almost always accompanied by Marsh 3 duodenal histopathological changes. Diagnosis of CD without biopsy may miss certain accompanying diseases, however in some cases with advanced examinations CD may be diagnosed by pediatric gastroenterology specialists without endoscopy.